Islamic Primary School Teachers' Perceptions on Digital Technology-Based Learning - Rofiatun Nisa (Cendekia, 2024)
Digital-based learning using e-learning is a suitable alternative for remote teaching and learning activities in response to what happens nowadays. In carrying out the e-learning activities from home, educators are required to autonomously access and understand the materials provided. The purpose of this study is to analyze primary school teachers' perceptions of digital-based learning using e-learning during the Covid-19 pandemic. This research is descriptive qualitative research employing data collection techniques through interviews with 12 teachers who apply e-learning in Lamongan Regency. The data validity was obtained using source triangulation. The data analysis techniques were yielded from data condensation, data display, and research conclusions. The results of this study indicated that as much as 68.75% of teachers claimed that digital technology-based learning using e-learning is in a good category, which means that with the help of e-learning in distance learning, teachers are aided, especially in overcoming problems that may occur when learning from home. For this reason, it is hoped that there will be a dissemination of insight development for all teachers about digital technology-based learning.